(3EHOGY MceI GdMcje aj HjGf HSe Gddg GdQMef GdQMjes - (3CMeO Hf eUWaj Hf YKeGf GdNGOej CHh fYje,J (B1165 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdPi LYd GdHSedI TQjYI ddGaJJGM GdQMef GdPi LYdgG dhUhd cd HQcI gh GdeaJGM s
(3BNQgG (B:s
(3Cf jPcQhfi HNGUI OYhGJge CLeYjf SLGf QHfG QH GdYRI YeG jUahf , hSdGe Ydi GdeQSdjf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B85 - (3Ui(B151s
(3GfXQgG HQbe (B12 (3ai gPG GdagQSs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B178 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B175s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B79 s
Keywords: (3GdeYGQa GdYGeIs